Anti-Inflammatory Effect of Fluvastatin on IL-8 Production Induced by Pseudomonas aeruginosa and Aspergillus fumigatus Antigens in Cystic Fibrosis - Jouneau, Stéphane; Bonizec, Mélanie; Belleguic, Chantal; Desrues, Benoit; Brinchault, Graziella; Galaine, Jeanne; Gangneux, Jean-Pierre; Martin-Chouly, Corinne (PloS one, 2011)
Early in life, patients with cystic fibrosis (CF) are infected with microorganisms including bacteria and fungi, particularly Pseudomonas aeruginosa and Aspergillus fumigatus. Since recent research has identified the anti-inflammatory properties of statins (besides their lipid-lowering effects), we investigated the effect of fluvastatin on the production of the potent neutrophil chemoattractant chemokine, IL-8, in whole blood from CF patients, stimulated by Pseudomonas aeruginosa (LPS) and Aspergillus fumigatus (AFA) antigens. Whole blood from adult patients with CF and from healthy volunteers was collected at the Rennes University Hospital (France). Blood was pretreated for 1 h with fluvastatin (0-300 µM) and incubated for 24 h with LPS (10 µg/mL) and/or AFA (diluted 1/200). IL-8 protein levels, quantified by ELISA, were increased in a concentration-dependent manner when cells were stimulated by LPS or AFA. Fluvastatin strongly decreased the levels of IL-8, in a concentration-dependent manner, in whole blood from CF patients. However, its inhibitory effect was decreased or absent in whole blood from healthy subjects. Furthermore, the inhibition induced by fluvastatin in CF whole blood was reversed in the presence of intermediates within the cholesterol biosynthesis pathway, mevalonate, farnesyl pyprophosphate or geranylgeranyl pyrophosphate that activate small GTPases by isoprenylation. For the first time, the inhibitory effects of fluvastatin on CF systemic inflammation may reveal the important therapeutic potential of statins in pathological conditions associated with the over-production of pro-inflammatory cytokines and chemokines as observed during the manifestation of CF. The anti-inflammatory effect could be related to the modulation of the prenylation of signalling proteins.